The Addition of High-Technology Into the Stop the Bleed Program Among School Personnel Improves Short-Term Skill Application, Not Long-Term Retention. Issue 6 (December 2021) - Jafri, Farrukh N.; Dadario, Nicholas B.; Kumar, Anshul; Silverstein, Samantha R.; Quintero, Frank; Larsen, Erik A.; Fasciglione, Kimberly; Mirante, Doreen; Ellsworth, Kelly; Amicucci, Bernadette; Ricca, Joseph
Abstract : Introduction: The Stop the Bleed (STB) program trains the general public on identifying and treating life-threatening bleeding. Data on efficacy and retention of skills taught through this program are limited, with the role of high-technology modalities to augment the program, such as simulation and feedback devices, untested. Methods: A convenience sample of 66 school personnel participated in an open-label observational study from January to August 2019. The control group received the standard bleeding control course, while the intervention group received the bleeding control course with addition of a simulation and a feedback device for wound packing. Assessment was performed by STB instructors using performance metrics from prior studies as well as a feedback device. Retention testing was performed 2 to 8 months after intervention. The study was approved by the hospital's institutional review board. Results: The intervention group performed better than the control group on correct tourniquet application [90.3% vs. 71.0%; odds ratio (OR) = 11.28; P = 0.015; 95% confidence interval (CI) = 1.86 to 104.67] wound packing scores (59.5% vs. 29.6%; OR = 0.33; P = 0.007; 95% CI = 9.36 to 56.00) and were more likely to assess their safety (OR = 5.49; P = 0.034; 95% CI = 1.28 to 27.66), and reported higher comfort scores on stepping into an emergency scenario (OR = 11.19; P = 0.004; 95% CI = 2.51 to 63.11), wound packing (OR = 5.16; P = 0.025; 95% CI = 1.35 to 22.46), and using a tourniquet (OR = 11.41; P = 0.003; 95% CI = 2.57 to 67.59). Thirty-one participants (46.9%) were assessed again at retention 2 to 8 months later where scores for tourniquet placement and wound packing were not significantly different in the two groups. Conclusions: Augmenting STB with simulation and feedback improved both self-reported comfort level and skill set of participants, but the retention of skills was poor in both groups. Abstract : Supplemental digital content is available in the text.